2016
DOI: 10.1111/jgs.13951
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor‐23 and Frailty in Elderly Community‐Dwelling Individuals: The Cardiovascular Health Study

Abstract: Objectives Both fibroblast growth factor 23 (FGF-23) and frailty have been previously associated with components of bone mineral metabolism, chronic disease states, and mortality. We sought to evaluate whether FGF-23 is related to frailty and to characterize the nature of their joint association with mortality. Design Cross sectional analysis and Cox proportional hazards mortality analysis. Setting The Cardiovascular Health Study Participants 2,977 community dwelling individuals. Measurements The predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
34
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 36 publications
7
34
1
2
Order By: Relevance
“…25 With regards to the associations of FGF-23 with individual clinical presentations of frailty observed in our study, some, but not all, are consistent with those reported in the study by Beben and colleagues. 25 These differential observations across the two studies may arise from heterogeneity in study population composition, including age and co-morbidities.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…25 With regards to the associations of FGF-23 with individual clinical presentations of frailty observed in our study, some, but not all, are consistent with those reported in the study by Beben and colleagues. 25 These differential observations across the two studies may arise from heterogeneity in study population composition, including age and co-morbidities.…”
Section: Discussionsupporting
confidence: 92%
“…Despite the importance of FGF-23 in bone mineral metabolism, its potential relationship with inflammation, and its observed association with age-related co-morbidities, only one study among elderly HIV-uninfected adults examined FGF-23’s association with frailty. 25 In this prior study, higher serum FGF-23 levels were associated with significantly higher odds of frailty. To our knowledge, no study has investigated this association in HIV-infected populations.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…FGF23 and Klotho mainly maintain urinary phosphorus excretion; any depleted activity of these molecules leads not only to hyperphosphatemia, but also to premature aging [27]. A higher FGF23 level is independently related to the prevalence of frailty in the community-dwelling elderly, even after adjustment for bone mineral metabolic markers such as phosphorus, calcium, parathyroid hormone, and vitamin D. Thus, endo-organ resistance to FGF23 in patients with frailty has been suggested [28].…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have reported higher FGF-23 levels in patients with an obesity, especially visceral fat accumulation [29], suggesting an indirect relationship with cardiovascular risk in patients with intact renal function. Aditionally, it was shown that FGF-23 is a marker of frailty among community-dwelling individuals [30]. Also, FGF-23 is related with arterial stiffness in diabetic patients, independently on estimated glomerular fi ltration rate [31].…”
Section: Fgf-23-α Klotho Axismentioning
confidence: 99%